Synthesis of Cellulose from Decorticated Sisal Plants (Agave sisalana) using the Acid Hydrolysis Method - Widyawati, Fauzi; Hidayat, Syamsul; Wiradana, Aditya; Setyaningtyas, Ayunda Kinasih; Bahtiar, Syamsul; Yanuar, Emsal (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Sisal Plant Production Process (Agave sisalana) produces waste of around 95%, which is wasted and can be an environmental problem because it is not processed properly. Sisal decortication waste contains active biochemical compounds, one of which is cellulose, which has the potential to be used in various fields. Cellulose is one of the most widely distributed and abundant biopolymers on Earth, as the main source of renewable materials obtained from plant fibers. Initial Treatment of Fiber Alkalization using 5% NaOH solution (1:20) for 2 hours at a temperature of 80 °C at a speed of 200 rpm. Then the bleaching process(bleaching). Samples of the results of alkalization treatment using hydrogen peroxide solution (H2THE23%) at a temperature of 80 °C for 3 hours, repeated once. In the Acid Hydrolysis process, the resulting sample is bleached with acid using sulfuric acid (H2SO465%) at a temperature of 80 °C for 1 hour (1:20). Sample Characterization Fiber characterization using the NDF test to determine cellulose content. The results of the cellulose content test in sisal fiber decortication waste were 1.545 mg/L Based on the results of the study, nanocellulose with a high % crystallinity was successfully extracted from sisal fiber decortication waste using a chemical treatment method. The FTIR spectrum shows a broad band at 3358-3410 cm-1which is the vibration of the OH group of cellulose. The removal of lignin levels was successfully carried out, showing that the peak of the spectrum band produced was only 1279.26 cm-1. The average size of nanocellulose particles is around 10-30 nm and consists of 30-100 cellulose molecules.